Development in Marketing : Building Prices, Place and Promotion at Slamet Hadipriyanto Batik, Banyumas - Feby Febrian; Granit Agustina; Rakhmia Nalibratawati; Adang Sutisna (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
The research was conducted in an effort to develop the marketing with the aim of establishing pricing, place, and promotion in the industry. The methodology applied in this study is qualitative, using a case study framework that combines exclusive interviews with owners, managers, and employees. By focusing on these aspects of the marketing mix, batik entrepreneurs A comprehensive marketing plan allows businesses to effectively reach their target audience, drive sales and build a strong brand presence. Strategies include understanding customer needs through market research, using digital channels like social media for visibility, creating compelling content and messaging, investing in paid advertising to target specific demographics, and analyzing performance to refine the overall strategy for growth and customer loyalty. Therefore, based on considerations of competitive and sustainable prices, strategic and centralized location placement, and the implementation of targeted and comprehensive promotional activities, it is expected that the quality of marketing in the batik industry can run effectively and efficiently through strengthening the development of a targeted and centralized marketing mix carried out by business actors. This approach clearly involves market segmentation, targeting, and positioning in order to adjust strategies to meet and complement needs and preferences. By focusing on these aspects of the marketing mix, batik entrepreneurs can effectively reach their target audience, increase sales, and build a strong brand presence in the market. A strategy that is able to stimulate customer buying interest is a very essential part in creating a diverse buyer community that always becomes a sustainable customer who participates in building and developing segmentation and sales targets for batik products in the region. In this study it was found developing marketing built through price, place and promotion in industry as a very important strategy in efforts to design and effective marketing campaigns to achieve business goals.